A New Model of Kalam Material Through Cybernetic Approach: Development Stages and The Influence Towards Speaking Skill of Students - Imron, Kristina; Irmansyah, Irmansyah; Nurhusna, Nurhusna; Maimunah, Iffat; Hajib, Zainal Abidin (Jurnal Al Bayan : Jurnal Jurusan Pendidikan Bahasa Arab, 2023)
Speaking skill is considered the most difficult to learn. On the other hand, speaking subject is considered a failure in providing competence to students. This can be proven by the lack of student's ability to speak Arabic and the value of learning outcomes. This study aimed to develop cybernetic-based kalam materials that can be used by students at the junior high school level as innovations in the use of teaching materials and learning theory. This research used the R&D method by adapting the six steps of Borg and Gall model development. Meanwhile, a small group trial was conducted on 24 students of an Islamic junior high school in Ogan Ilir, using by purposive random sampling technique. This research resulted in kalam material products using the Canva application. The validation of material experts is 84% and media experts get 90.76% so it can be concluded that the product developed is suitable for use with the revisions suggested by validators.  Based on the comparison of pretest results showed an average of 48.33 and the post-test results were 78.33. Then continued with the nonparametric test, namely the Wilcoxon test. This test was chosen because the data is not distributed normally. Asimp Wilcoxon. Sage. (2-tailed) equals 0.000. Since the value of 0.000 is less than 0.05, it can be concluded that the "hypothesis is acceptable". The results of the effectiveness test showed the development of Cybernetic-based speaking materials in improving knowledge and skills in speaking languages.